SUICIDE NOTE IN LIGATURE - A CASE REPORT - Ghosh, Mithun; Singh, Bhim (Journal of Forensic Medicine and Toxicology, 2017)
Suicide is a leading cause of death among young adults. About a million suicides occur annually throughout the world. A suicide note is often found at the scene. It has been reported that a note was left in 5%-43% of the suicides1. The content of a suicide note include apology, shame, guilt, love for those left behind and instruction regarding practical affairs2.It is an important tool for medico-legal investigation on the manner and circumstances surrounding the death. The victim generally writes them on a paper, notebook, wall, or mirror by means of pen or marker3. We present a case where suicide note was recovered from the ligature itself. This method of keeping a suicide note in the ligature is unique and rarely found in the literature.
Keywords: vulnerability; often found